Development of solar powered food truck with security monitoring system - Alil, Siti Norhuqaimah; Abdullah, Mohd Noor; Islam, Syed Zahurul (Penerbit UTHM, 2020)
Due to global decline in fossil fuel reserves and contribution on their emissions (during the extraction, production and utilization process) to climate change, many countries including Malaysia are now examining their national energy policies with a view of shifting toward low-carbon and renewable sources of energy. Solar energy is the most promising backup energy as it has many advantages over other resources. Solar energy is a naturally available and clean energy source derived from sun that can be exploited directly to generate electricity [1]. No release the pollutant, low maintenance and high reliability with life span expectation of 20 – 30 years made solar power a favourable source energy to be used in the future ..